2021
DOI: 10.1111/evo.14373
|View full text |Cite
|
Sign up to set email alerts
|

Sperm depletion in relation to developmental nutrition and genotype in Drosophila melanogaster

Abstract: Nutrient limitation during development can restrict the ability of adults to invest in costly fitness traits, and genotypes can vary in their sensitivity to developmental nutrition. However, little is known about how genotype and nutrition affect male ability to maintain ejaculate allocation and achieve fertilization across successive matings. Using 17 isogenic lines of Drosophila melanogaster, we investigated how variation in developmental nutrition affects males' abilities to mate, transfer sperm, and sire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 82 publications
(215 reference statements)
0
17
0
Order By: Relevance
“…However, even if high‐quality males mate more often, they might continue to transfer more SP compared with low‐quality males, either because they store more SP or because they replenish SP more rapidly, which will tend to restore quality dependence in SP transfer. An analogous process presumably underlies the condition dependence of male reproductive potential in some Drosophila species, in which only high‐quality males can maintain the transfer of very long, costly sperm over successive matings (Lüpold et al ., 2016; see also Macartney et al ., 2021). Even in the face of noisiness in the relationship between SP transfer and male quality, females might integrate information from multiple sources to assess male quality more accurately.…”
Section: The Evolution Of Sp Functionmentioning
confidence: 99%
“…However, even if high‐quality males mate more often, they might continue to transfer more SP compared with low‐quality males, either because they store more SP or because they replenish SP more rapidly, which will tend to restore quality dependence in SP transfer. An analogous process presumably underlies the condition dependence of male reproductive potential in some Drosophila species, in which only high‐quality males can maintain the transfer of very long, costly sperm over successive matings (Lüpold et al ., 2016; see also Macartney et al ., 2021). Even in the face of noisiness in the relationship between SP transfer and male quality, females might integrate information from multiple sources to assess male quality more accurately.…”
Section: The Evolution Of Sp Functionmentioning
confidence: 99%
“…To win the intense sperm competition, Drosophila males produce long spermatozoa, resulting in larger costs of sperm production. Indeed, it is found that nutrient diet during development affects the amount of sperm transferred to female in D. melanogaster (Macartney et al 2021) and that the number of sperm bundles that the male contains is positively correlated with male body size in D. hydei (Pitnick and Markow 1994a). In spider mites, females use sperm only from the rst mating if the mating is not disturbed, yet readily mate multiple times (Rodrigues et al 2020) indicating that sperm competition is present but not as strong as in fruit ies.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we manipulated the resources available to developing males, allowed these males to mate with a virgin female after reaching sexual maturity, and then identified ejaculate proteins from the female bursa copulatrix immediately after copulation. Although arthropod ejaculates can also be affected by adult diet [29], we manipulated larval diet as the metabolism, tissue growth and reproductive function of holometabolous insects are particularly sensitive to diet during development [30][31][32][33][34][35]. Larval diet manipulation may therefore affect a male's resource allocation to sexual traits, including costly ejaculate components at least in early adult life [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%